Employing CO2 as reaction medium for in-situ suppression of the formation of benzene derivatives and polycyclic aromatic hydrocarbons during pyrolysis of simulated municipal solid waste. (May 2017) - Lee, Jechan; Choi, Dongho; Tsang, Yiu Fai; Oh, Jeong-Ik; Kwon, Eilhann E.
Abstract: This study proposes a strategic principle to enhance the thermal efficiency of pyrolysis of municipal solid waste (MSW). An environmentally sound energy recovery platform was established by suppressing the formation of harmful organic compounds evolved from pyrolysis of MSW. Using CO2 as reaction medium/feedstock, CO generation was enhanced through the following: 1) expediting the thermal cracking of volatile organic carbons (VOCs) evolved from the thermal degradation of the MSWs and 2) directly reacting VOCs with CO2 . This particular influence of CO2 on pyrolysis of the MSWs also led to the in-situ mitigation of harmful organic compounds ( e.g., benzene derivatives and polycyclic aromatic hydrocarbons (PAHs)) considering that CO2 acted as a carbon scavenger to block reaction pathways toward benzenes and PAHs in pyrolysis. To understand the fundamental influence of CO2, simulated MSWs ( i.e., various ratios of biomass to polymer) were used to avoid any complexities arising from the heterogeneous matrix of MSW. All experimental findings in this study suggested the foreseeable environmental application of CO2 to energy recovery from MSW together with disposal of MSW. Graphical abstract: Highlights: CO2 mitigates the formations of benzene derivatives and PAHs in pyrolysis of MSW. CO2 acts as a carbon scavenger to mitigate air pollutants. CO2 increases gaseous products from pyrolysis of MSW. CO2 enhances the production of CO from pyrolysis of MSW.